2017
DOI: 10.1186/s12889-017-4883-6
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and health in China: exploring the mediating role of lifestyle

Abstract: BackgroundAlthough social capital as a key determinant of health has been well established in various studies, little is known about how lifestyle factors mediate this relationship. Understanding the cross-relationships between social capital, health, and lifestyle factors is important if health promotion policies are to be effective. The purpose of this study is to explore whether different dimensions of social capital and lifestyle factors are related, and whether lifestyle factors mediate the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 57 publications
3
35
0
1
Order By: Relevance
“…Specifically, our findings confirmed that cultural and social capital obviously promoted physical exercise behavior, which was in line with previous studies [ 50 , 51 ]. Besides, among the three forms of capital, cultural capital was the most influential determinant of physical exercise.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, our findings confirmed that cultural and social capital obviously promoted physical exercise behavior, which was in line with previous studies [ 50 , 51 ]. Besides, among the three forms of capital, cultural capital was the most influential determinant of physical exercise.…”
Section: Discussionsupporting
confidence: 92%
“…Main social capital constructs are trust , social participation , informal control and social cohesion , but the operationalization of each of these constructs is mostly heterogeneous from study to study. Some researches also combined measures of network social capital and social support. Only 10 out of the 22 studies included in this review provided information on the operationalization of social capital at the neighbourhood level .…”
Section: Resultsmentioning
confidence: 99%
“…(40,43,48,49) and social cohesion (40,43,55,57), but the operationalization of each of these constructs is obesity reviews mostly heterogeneous from study to study. Some researches (37,38,43,47,54,57) also combined measures of network social capital and social support. Only 10 out of the 22 studies included in this review provided information on the operationalization of social capital at the neighbourhood level (21,44,(50)(51)(52)(55)(56)(57)(58).…”
Section: Social Cohesionmentioning
confidence: 99%
“…Despite finding association of social capital with CMD and depression, it is known that to evaluate mental health, one should understand its complexity and multiple factors involved, and thus one should consider the role of social capital when isolated of possible behavioral mediators in health (such as nutrition, physical activity and smoking) [41]. In addition, the ELSA-Brasil cohort is made of public servants.…”
Section: Discussionmentioning
confidence: 99%